(3McGjIs - (3YHO Gddg Hf eMeO Hf GdSjO GdHWdjhSj, GHf GdSjO GdHWdjhSj, CHh eMeO J (B521 (3g` s
(3ChdgG (B:s
(3bGd GHh eMeO YHO Gddg GdHWdjhSi ONd Ydi ai HYV GdYTjGJ HYV ENhGfi hgh jcKQ GdJgdjd hGdJSHjM s
(3BNQgG (B:s
(3fLRJ GdMcGjI HMeO Gddg hYhfg s
(3Vef eLehY , JQJjHgG (B: 2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B268s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs